2023
DOI: 10.1002/adma.202303489
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Confined Silver Nanoparticles in Mercapto Metal–Organic Frameworks to Compartmentalize Li Deposition Toward Anode‐Free Lithium Metal Batteries

Abstract: As the promising next‐generation energy storage solution, lithium metal battery (LMB) has gained great attention but still suffers from troubles associated with the highly active metallic lithium. Herein, it is aimed to develop an anode‐free LMB engaging no Li disk or foil by modifying the Cu current collector with mercapto metal–organic frameworks (MOFs) impregnating Ag nanoparticles (NPs). While the polar mercapto groups facilitate and guide Li+ transport, the highly lithiophilic Ag NPs help to enhance the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 77 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…The Ag 3d spectrum of Cat 2 shows peaks at 368.2 and 374.2 eV with a gap of 6.0 eV, corresponding to Ag 3d 5/2 and Ag 3d 3/2 , respectively, confirming the presence of the zero oxidation of silver (Ag 0 ; Figure 3b). 40,94 The characteristic peak of thiol was observed as an S 2p peak in UiO-66-NH-SH (1) (164.5; Figure 3c), which shifted to 164.1 (Figure 3d) in Ag nanoparticle-functionalized Cat 2, confirming the strong interaction between thiol and Ag, which correlates well with the previously reported literature. 40,95 In the case of N 1s and O 1s, a very slight shift is observed between the thiol MOF and the catalyst, which excludes the strong interaction between N, O, and Ag (Figure 3d).…”
Section: ■ Introductionssupporting
confidence: 89%
“…The Ag 3d spectrum of Cat 2 shows peaks at 368.2 and 374.2 eV with a gap of 6.0 eV, corresponding to Ag 3d 5/2 and Ag 3d 3/2 , respectively, confirming the presence of the zero oxidation of silver (Ag 0 ; Figure 3b). 40,94 The characteristic peak of thiol was observed as an S 2p peak in UiO-66-NH-SH (1) (164.5; Figure 3c), which shifted to 164.1 (Figure 3d) in Ag nanoparticle-functionalized Cat 2, confirming the strong interaction between thiol and Ag, which correlates well with the previously reported literature. 40,95 In the case of N 1s and O 1s, a very slight shift is observed between the thiol MOF and the catalyst, which excludes the strong interaction between N, O, and Ag (Figure 3d).…”
Section: ■ Introductionssupporting
confidence: 89%
“…With the increase in the amount of Ag, the ICE of the electrode increased gradually, which could be attributed to the guiding effect of Ag nanoparticles on the deposition of lithium ions on the anode before the cycle. 50,51 Charge–discharge profiles indicated that pSi/Ag-5 exhibited the shortest SEI film-forming process ahead of the voltage plateau during the initial charge process, validating the pre-deposition of lithium ions. However, for pSi/Ag-10, the Ag particles that were larger than the expected size may take up an excessive amount of the internal volume of the porous Si, exerting additional pressure on the expanded Si matrix during the initial lithiation process, which may result in the fracturing of the Si particles and the formation of excessive SEI film.…”
Section: Resultsmentioning
confidence: 78%
“…The value of Li ion diffusion coefficient ( D Li ) could be calculated using the eqn (1): D Li = ( R 2 T 2 )/(2 A 2 n 4 F 4 C 4 σ 2 )where R is the universal gas constant, T is the absolute temperature, A is the electrode area, n is the number of transferred electrons, F is Faraday's constant, and C is the concentration of Li + . 48–50 The value of σ can be obtained by the relationship between Z ′ and ω −1/2 , which can be expressed using eqn (2): 48 Z ′ = ( R e + R ct + σω −1/2 )The low-frequency range fitting results are illustrated in Fig. 8c and d.…”
Section: Resultsmentioning
confidence: 99%
“…The valuable applications of Zr-DMBD are due to this free-standing thiol group; since it is very reactive and easily functionalizable, there are numerous opportunities for post-synthetic modifications for specific applications. 97–107 All reported post-synthetic modifications of Zr-DMBD for their significant applications are listed in Table 4. Compounds derived from Zr-DMBD via post-synthetic methods have extensive use spanning multiple domains.…”
Section: Synthesis and Structure Of Thiol And Thioether-based-acid Li...mentioning
confidence: 99%
“…Recently Li et al utilized Ag@Zr-DMBD to to achieve reversible stripping, which shows a specific capacity of 159.8 mA h g −1 . 107…”
Section: Applicationsmentioning
confidence: 99%